The boy who grew dragons - Shepherd, Andy; Ogilvie, Sara, 1971- (2018)
"When Tomas discovers a strange old tree at the bottom of his grandad's garden, he doesn't think much of it. But he takes the funny fruit from the tree back into the house - and gets the shock and delight of his life when a tiny dragon hatches! The tree is a dragonfruit tree, and Tomas has got his very own dragon, Flicker ... Tomas soon finds out that life with Flicker is great fun, but also very ... unpredictable. Yes, dragons are wonderful, but they also set fire to your toothbruth and leave your pants hanging from the TV aerial. Tomas has to learn how to look after Flicker - and quickly. And then something extraordinary happens - more dragonfruits appear on the tree. Tomas is officially growing dragons ..."--Publisher's description.